2013
DOI: 10.1088/1475-7516/2013/09/034
|View full text |Cite
|
Sign up to set email alerts
|

Stability of BEC galactic dark matter halos

Abstract: In this paper we show that spherically symmetric BEC dark matter halos, with the sin r/r density profile, that accurately fit galactic rotation curves and represent a potential solution to the cusp-core problem are unstable. We do this by introducing back the density profiles into the fully time-dependent Gross-Pitaevskii-Poisson system of equations. Using numerical methods to track the evolution of the system, we found that these galactic halos lose mass at an approximate rate of half of its mass in a time sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 24 publications
1
44
0
Order By: Relevance
“…More recently, this result was confirmed using a simple thermodynamic argument [22]. On the other hand, Guzman [23] found that the self-gravitating BEC halos described in [20] are unstable, and that furthermore, a relationship exists between the halo size and the BEC self-interaction parameter, which may be untenable (see also [24]). However, Toth [25] showed that these difficulties arise from the inappropriate application of the Thomas-Fermi approximation, and recommended the use of a different density profile as an approximate static solution.…”
Section: Arxiv:14127152v1 [Hep-ph] 22 Dec 2014mentioning
confidence: 81%
See 1 more Smart Citation
“…More recently, this result was confirmed using a simple thermodynamic argument [22]. On the other hand, Guzman [23] found that the self-gravitating BEC halos described in [20] are unstable, and that furthermore, a relationship exists between the halo size and the BEC self-interaction parameter, which may be untenable (see also [24]). However, Toth [25] showed that these difficulties arise from the inappropriate application of the Thomas-Fermi approximation, and recommended the use of a different density profile as an approximate static solution.…”
Section: Arxiv:14127152v1 [Hep-ph] 22 Dec 2014mentioning
confidence: 81%
“…Is a Bose star stable? Guzmán et al argued [23] that it is not. However, the mass profiles [18] that they examined were constructed on the basis of the Thomas-Fermi approximation.…”
Section: B Numerical Stabilitymentioning
confidence: 99%
“…Thus despite the sharp cut-off of the halo density, the BEC dark matter candidate is consistent with the rotation curve data of all types of galaxies [23]. The dynamics of rotating Bose Condensate galactic dark matter halos, made of an ultralight spinless bosons, and the impact of the halo rotation on the galactic rotation curves was analyzed in [24].…”
Section: Introductionmentioning
confidence: 59%
“…therein. These models embody plausible features of cold dark matter, in some respects showing advantages, but they may also have their own difficulties such as e.g., the problem of (gravitational) collapse [48], or overestimated total mass of DM halos for dwarf galaxies [46]. This motivates researchers to explore other models that would be free of the weak points.…”
Section: Application For Modeling Dark Mattermentioning
confidence: 99%